Glycerol Is an Osmoprotectant in Two Antarctic Chlamydomonas Species From an Ice-Covered Saline Lake and Is Synthesized by an Unusual Bidomain Enzyme - Raymond, James A.; Morgan-Kiss, Rachael; Stahl-Rommel, Sarah (Frontiers in Plant Science, 2020)
Glycerol, a compatible solute, has previously been found to act as an osmoprotectant in some marine Chlamydomonas species and several species of Dunaliella from hypersaline ponds. Recently, Chlamydomonas reinhardtii and Dunaliella salina were shown to make glycerol with an unusual bidomain enzyme, which appears to be unique to algae, that contains a phosphoserine phosphatase and glycerol-3-phosphate dehydrogenase. Here we report that two psychrophilic species of Chlamydomonas (C. spp. UWO241 and ICE-MDV) from Lake Bonney, Antarctica also produce high levels of glycerol to survive in the lake’s saline waters. Glycerol concentration increased linearly with salinity and at 1.3 M NaCl, exceeded 400 mM in C. sp. UWO241, the more salt-tolerant strain. We also show that both species expressed several isoforms of the bidomain enzyme. An analysis of one of the isoforms of C. sp. UWO241 showed that it was strongly upregulated by NaCl and is thus the likely source of glycerol. These results reveal another adaptation of the Lake Bonney Chlamydomonas species that allow them to survive in an extreme polar environment.